miR-10a Regulates Proliferation of Human Cardiomyocyte Progenitor Cells by Targeting GATA6 - Liang, Dandan (Public Library of Science, 2014)
microRNAs (miRNAs) play essential roles in cardiogenesis. The altered expression of miRNAs can result in cardiac malformations by inducing abnormalities in the behavior of cardiac cells. However, the role of miR-10a in the regulation of cardiomyocyte progenitor cells (CMPCs) remains undetermined. In the present study, we found that up- or down-regulation of miR-10a inhibited or promoted the proliferation of human CMPCs, respectively, without affecting their differentiation toward cardiomyocytes. miR-10a bound to GATA6 directly and reduced GATA6 expression. Over-expression of GATA6 greatly attenuated the miR-10a-mediated inhibitory effect on the proliferation of human CMPCs. Thus, our results indicate that miR-10a could effectively modulate the proliferation of human CMPCs by targeting GATA6. The finding provides novel insights into the potency of miR-10a during heart development.